Abundance And Distribution Pattern BivalviaDonax Cunneatus andDonax Deltoides on the Intertidal Zone of Pantai Surantih, Regencyof South Coast, of West Sumatera Province - Dimas Agung Guntara; Afrizal Tanjung; Elizal Elizal (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
AbstractThis study was conducted in the intertidal zone of Surantih Beach, South Coast Regency, in the West Sumatra province. It aims to learn the distribution pattern and abundance of bivalves (D. cunneatus and D. deloides). Sampling locations were chosen purposively with different characteristic. The field samples were collected with shovel along the transect line then filtered with 1 sq. mm in size for further analysis in the lab. The result showed that these two species are found, namely, D. cunneattus and D. deltiodes. The abundance of these bivalves in the intertidal of Surantih Beach ranges from 2.83 -3.63 individual per sq. meter where the highest one was found in the third station. These species have aggregated distribution structures in the area under study.Keywords: Bivalvia, Intertidal Zone, D. Cunneatus, D. Deltoides, Abundance, Distribution Patterns, Surantih Beach.